Multidigit tactile perception I: motion integration benefits for tactile trajectories presented bimanually - Arslanova, Irena; Takamuku, Shinya; Gomi, Hiroaki; Haggard, Patrick (Journal of Neurophysiology, 2022)
Object manipulation involves encoding spatially and temporally extended tactile signals, yet most studies emphasize minimal units of tactile perception (e.g., selectivity). Instead, we asked participants to average two tactile motion trajectories delivered simultaneously to two different fingerpads. Our results show strong integration between multiple tactile inputs, but subject to limitations for inputs delivered within a hand. As such, the present study establishes a paradigm for studying unified experience of touch despite distinct stimulus elements. Interactions with objects involve simultaneous contact with multiple, not necessarily adjacent, skin regions. Although advances have been made in understanding the capacity to selectively attend to a single tactile element among distracting stimulations, here, we examine how multiple stimulus elements are explicitly integrated into an overall tactile percept. Across four experiments, participants averaged the direction of two simultaneous tactile motion trajectories of varying discrepancy delivered to different fingerpads. Averaging performance differed between within- and between-hands conditions in terms of sensitivity and precision but was unaffected by somatotopic proximity between stimulated fingers. First, precision was greater in between-hand compared with within-hand conditions, demonstrating a bimanual perceptual advantage in multi-touch integration. Second, sensitivity to the average direction was influenced by the discrepancy between individual motion signals, but only for within-hand conditions. Overall, our experiments identify key factors that influence perception of simultaneous tactile events. In particular, we show that multi-touch integration is constrained by hand-specific rather than digit-specific mechanisms. NEW & NOTEWORTHY Object manipulation involves encoding spatially and temporally extended tactile signals, yet most studies emphasize minimal units of tactile perception (e.g., selectivity). Instead, we asked participants to average two tactile motion trajectories delivered simultaneously to two different fingerpads. Our results show strong integration between multiple tactile inputs, but subject to limitations for inputs delivered within a hand. As such, the present study establishes a paradigm for studying unified experience of touch despite distinct stimulus elements.